Psychometric evaluation of the thin-ideal internalization scale (tiis) for Brazilian young women - Lourenço, Juliana Aparecida Alves; Amaral, Ana Carolina Soares; Ferreira, Maria Elisa Caputo (Paidéia (Ribeirão Preto), 2021)
Internalization is an important dimension of body image, which can be assessed using the Thin-Ideal Internalization Scale (TIIS). This study aims to carry out the cross-cultural adaptation and psychometric assessment of the TIIS for young Brazilian women. A total of 448 young university women participated in the research (Mage = 21.4 years; SD = 2.91). Exploratory and confirmatory factor analysis, association with body dissatisfaction (Body Shape Questionnaire-8) and eating attitudes (Eating Attitudes Test-26), and assessment of reliability (internal consistency and test-retest) were performed. The instrument had its semantic, idiomatic, cultural and conceptual equivalences ensured. The factor analysis demonstrated the presence of three factors and satisfactory adjustment indexes. In addition, the scale showed adequate values for convergent validity and reliability. The final version of the TIIS (18 items) obtained adequate psychometric properties for the evaluation of the body-ideal internalization among Brazilian young women. We suggest new studies to prove the factor structure for other populations.